Thyroid function assessment before and after diagnosis of schizophrenia: A community-based study - Melamed, Shirel Barnea; Farfel, Alon; Gur, Shay; Krivoy, Amir; Weizman, Shira; Matalon, Andre; Feldhamer, Ilan; Hermesh, Haggai; Weizman, Abraham; Meyerovitch, Joseph (Psychiatry research, 2020)
Alterations in thyroid hormone levels may affect brain and mental disorders. Conversely, schizophrenia and its antipsychotic treatments can affect thyroid hormone levels. However, data on thyroid hormone levels during the course of schizophrenia disorder are scant. The aim of the study was to assess the rate of thyroid hormone disorders in outpatients before and after diagnosis of schizophrenia. A retrospective matched-control design was used. The cohort included 1252 patients suffering from ICD-10 schizophrenia, and 3756 control subjects matched for gender, age, socioeconomic status, and origin. All were identified from the database of a large health management organization. The pertinent clinical data were collected from the electronic medical records. There was no significant between-group difference in the distribution of thyroid-stimulating hormone levels. Before diagnosis, both groups had a similar rate of hypothyroidism. After diagnosis of schizophrenia and initiation of antipsychotic treatment, the rate of hypothyroidism was significantly higher in the patient group. It remained significantly higher after exclusion of patients receiving lithium. The increased rate of hypothyroidism in patients with schizophrenia after, but not before, the diagnosis of schizophrenia suggests that antipsychotic medications may affect thyroid hormone levels. Screening for thyroid disorders is warranted in patients with schizophrenia under antipsychotic treatment.